Specialized acyl carrier protein used by serine palmitoyltransferase to synthesize sphingolipids in Rhodobacteria - Padilla-Gómez, Jonathan; Olea-Ozuna, Roberto Jhonatan; Contreras-Martínez, Sandra; Morales-Tarré, Orlando; García-Soriano, Daniela A.; Sahonero-Canavesi, Diana X.; Poggio, Sebastian; Encarnación-Guevara, Sergio; López-Lara, Isabel M.; Geiger, Otto (Frontiers in Microbiology, 2022)
Serine palmitoyltransferase (SPT) catalyzes the first and committed step in sphingolipid biosynthesis condensating L-serine and acyl-CoA to form 3-oxo-sphinganine. Whenever the structural gene for SPT is present in genomes of Rhodobacteria (α-, β-, and γ-Proteobacteria), it co-occurs with genes coding for a putative acyl carrier protein (ACP) and a putative acyl-CoA synthetase (ACS). In the α-proteobacterium Caulobacter crescentus, CC_1162 encodes an SPT, whereas CC_1163 and CC_1165 encode the putative ACP and ACS, respectively, and all three genes are known to be required for the formation of the sphingolipid intermediate 3-oxo-sphinganine. Here we show that the putative ACP possesses a 4´-phosphopantetheine prosthetic group, is selectively acylated with palmitate by the putative ACS and therefore is a specialized ACP (AcpR) required for sphingolipid biosynthesis in Rhodobacteria. The putative ACS is unable to acylate coenzyme A or housekeeping ACPs, but acylates specifically AcpR. Therefore, it is a specialized acyl-ACP synthetase (AasR). SPTs from C. crescentus, Escherichia coli B, or Sphingomonas wittichii use preferentially acyl-AcpR as thiol substrate for 3-oxo-sphinganine synthesis. Whereas acyl-AcpR from C. crescentus is a good substrate for SPTs from distinct Rhodobacteria, acylation of a specific AcpR is achieved by the cognate AasR from the same bacterium. Rhodobacteria might use this more complex way of 3-oxo-sphinganine formation in order to direct free fatty acids towards sphingolipid biosynthesis.